Laser surface re-melting of additive manufactured samples with a line focused beam. (2020) - Kumar, Abhishek; Saha, Suman; Kumar, C.S.; Nath, A.K.
Abstract: The laser polishing mechanism is based on the fusion of a micro layer of material due to the action of the high temperature laser beam. Laser polishing, also known as laser surface remelting, involves melting a thin layer of the substrate, with surface tension causing the material to flow from peaks to valleys. In laser polishing, the material is not removed; rather it is relocated as a molten pool. The laser beam with sufficient energy density is first allowed to quickly fuse a layer on the substrate surface of microscopic thickness. Accordingly, the peaks of the asperities on the substrate surface are fused. Owing to the fluidity of this molten metal, it easily flows into the adjacent valleys of the asperities on the surface. The same molten layer is then allowed to re-solidify so that solidified layer remains adhered to the substrate surface. This, in turn, diminishes the peaks and valleys of the asperities, which ultimately results in a smoother surface. Since surface roughness is one major limitation of additive manufacturing components, so this article makes an attempt to address the roughness of such components. The capability of laser polishing (or laser surface remelting) in reducing surface roughness is explored for various beam power and scan speed. The better set of parameters for this purpose are presented. A final surface roughness in the range of 1.0–1.1 μm is obtained for three different set of parameters. 85% reduction in surface roughness due to laser polishing is also observed.